Implementación de los manuales de funciones y evaluación del desempeño de los funcionarios de la empresa Administradora Seguros y CIA. Ltda. (2014)
Identify the functions of the partners of a company and subsequently evaluate the performance is a basic work of the administrators as it strengthens the organizational performance and increases the sense of belonging of the employees making them partakers of the strategic planning. Through the job a review was able to be performed and further socialization of the existing manuals, the functions currently performed were analyzed with each employee and adjustments were proposed for these manuals, the performance was assessed and obtained results were socialized to make commitments for improvement. Of the five subsystems of the ARH posed by Idalberto Chiavenato, it delved into the 2nd (application), where the description and analysis of positions and performance evaluation is found.